WHY THEY STAYED: NEAR-PERFECT RETENTION IN AN ONLINE CERTIFICATION PROGRAM IN LIBRARY MEDIA - Katrina A. Meyer; Janis Bruwelheide; Russell Poulin (Online Learning, 2019)
This paper focuses on an assessment of an online certification program in K–12 library media which has a near-perfect record of retaining students. Students and graduates of the program were asked to identify reasons for enrolling (and staying enrolled) in the program as well as functions that faculty performed well. These reasons were drawn upon three theoretical models of student retention: Tinto, Bean and Metzner, the Community of Inquiry Model, plus advantages of online programs. Openended questions and Likert-style items provide some support for the academic integration portion of Tinto’s retention model, Bean and Metzner’s retention model for adult non-traditional students, and the importance of the program being available online in explaining why students stayed. Open-ended questions and Likert-style items also support the use of the Community of Inquiry model as a way of identifying what faculty did well in the program and perhaps contributed to the students’ willingness to stay enrolled in the program.